Collagen filler, preparation method and application thereof

The preparation of collagen fillers with controllable pore structures through the dynamic template method solves the problem of easy degradation and toxicity risks of collagen fillers after implantation in the prior art, and achieves long-term maintenance and high biocompatibility.

CN117618671BActive Publication Date: 2025-03-25YANTAI DESHENG MARINE BIOTECHNOLOGY CO LTD

Patent Information

Application Number
CN202311711140.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-13
Publication Date
2025-03-25
Estimated Expiration
2043-12-13

AI Technical Summary

Technical Problem

After implanting into the human body, the support effect of existing collagen fillers is not ideal, it is prone to displacement, and it is prone to degradation in a short period of time and loses the ability to fill tissues, which poses a risk of toxicity caused by excessive crosslinking.

Method used

Collagen fillers were prepared by dynamic template method, and the cross-linked structure of collagen fiber bundles was regulated by controlling the pore size and addition order of the microspheres to form a fiber mesh-like graded porous structure with controllable pore structure.

Benefits of technology

The long-term maintenance of collagen fillers is achieved, which improves its anti-enzymatic properties and biocompatibility in the body, reduces the risk of crosslinking agent residues, and enhances the safety and effectiveness of the fillers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117618671B_ABST
    Figure CN117618671B_ABST
Patent Text Reader

Abstract

The present invention relates to a collagen filler with a controllable pore structure, wherein the collagen filler has an average pore size D 50 The invention also relates to a method for preparing a collagen filler and a use of the collagen filler of the invention.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of medical biomaterials, in particular, to a collagen filler with a controllable pore structure and its application. The present invention also relates to a preparation method of the collagen with a controllable pore structure of the present invention and the application of the collagen with a controllable pore structure of the present invention. Background Art

[0002] Collagen is a natural protein. As the main component of skin tissue, it is an ideal material for correcting and repairing soft tissue defects. Collagen exists in the form of fibers and is a common component of connective tissue. It accounts for about 30% of the total protein in the human body and is an indispensable matrix skeleton for organs and tissues. As a cell growth attachment and scaffold, collagen fibers can induce the migration, proliferation and differentiation of fibroblasts and epithelial cells, and partially participate in the nutrient transport and metabolism of tissues and organs. In addition, with the increasing maturity of collagen extraction and purification technology, its immunogenicity and other risks have also been reduced to a low level, or even negligible. Therefore, compared with other filling materials, collagen has advantages in physical properties and biological properties that other materials cannot match. However, on the market, fillers with collagen as the main component usually show unsatisfactory support effects after implantation into the human body, are prone to displacement, and are prone to degradation in a short period of time and lose tissue filling ability, or cause a series of toxic risks due to excessive cross-linking.

[0003] In view of the technical difficulties existing in the field of collagen fillers, CN113768815A discloses a collagen implant and a preparation method thereof. The purity of the collagen prepared by the method is as high as 99.82%, showing higher activity and safety. After the collagen molecules self-aggregate, a fiber structure with a distinct shape is formed. Each fiber is fully exposed and interlaced to form a fiber network. The fiber thickness is uniform, forming better elastic strength. Then, because the implant is not cross-linked to increase the maintenance time, the results show that its degradation loss rate at 3 months has reached about 40%. Although compared with other non-cross-linked collagen implants, this product has certain advantages in anti-enzymatic properties, but its degradation loss rate is still much higher than that of cross-linked collagen implants.

[0004] CN114288469A discloses the composition and preparation method of a double cross-linked collagen filler, which double cross-links collagen fibers with reducing monosaccharides and carbodiimide. Data show that the melting point is higher after double cross-linking than single cross-linking, but the melting point of 66.6°C is still at a medium level among cross-linked collagen implants. In addition, the implant homogenization process is cryo-ball milling, which may destroy the network structure of the collagen fiber overlap to a certain extent while improving the homogenization efficiency, thereby affecting the support effect and tissue metabolism efficiency of the filler after implantation into the tissue.

[0005] CN102924731B discloses a triple cross-linked collagen, a manufacturing method and a use, wherein the collagen suspension is cross-linked three times step by step, and different types of cross-linking agents are used at each stage, so that the cross-linked product has a high degree of cross-linking, a high melting point and a low enzymatic hydrolysis rate, so that the product can be maintained longer during the filling and repair process. However, triple cross-linking also brings more risks of cross-linking agent residues to the product, and the use of multiple cross-linking agents in a product brings more risks of sensitization, teratogenesis or potential toxicity to clinical patients. Moreover, in the cleaning process after cross-linking, it is only washed three times with PBS greater than 10 times the volume, that is, the product only reduces the cross-linking agent concentration to one thousandth of its original total amount in the cleaning process, which increases the risk of more cross-linking agent residues due to incomplete cleaning, thereby causing its toxicity risk in product application.

[0006] In view of the above reasons, there is an urgent need for a tissue filler, such as a skin tissue filler, that has good supporting and shaping ability, longer maintenance time, and excellent biocompatibility and safety synergy. The collagen filler of the present invention has a controllable pore structure, good mechanical properties, and a maintenance time that is more in line with the expected filling effect. The present invention also relates to a preparation method thereof, which can provide a product with better performance and safer safety for the current collagen filler products. Summary of the invention

[0007] The collagen filler disclosed in the present invention overcomes the disadvantages of known implants. One of the purposes of the present invention is to provide a collagen filler with a controllable pore structure, good supporting and shaping effect, higher dynamic viscosity, and a maintenance time that meets the intended use.

[0008] The collagen filler disclosed in the present invention has a large pore size, a high porosity, a low cross-linking degree, and still has good resistance to enzymolysis. It can maintain a long time in in vitro and in vivo degradation tests and can maintain a long filling time. Due to the structure of the product, it is not only conducive to the growth, proliferation and differentiation of cells, but also provides more convenience for the transportation and metabolism of nutrients in tissues to synergistically promote collagen fiber regeneration; in terms of product safety and effectiveness, the mild cross-linking process enables the product to maintain a low cross-linking degree and high biological activity. In particular, its sufficient and thorough cross-linking efficiency also improves the resistance to enzymolysis of collagen and prolongs the maintenance time of the product, thereby achieving a synergistic effect in terms of safety and effectiveness.

[0009] According to one embodiment of the present invention, the average pore size D of the collagen filler of the present invention is s0It is 50 μm to 500 μm, preferably 80 μm to 400 μm, even 90 μm to 300 μm, especially 100 μm to 250 μm, and particularly 120 μm to 200 μm.

[0010] According to another embodiment of the present invention, the porosity of the collagen filler of the present invention is 80%-99.5%, even 85%-98%, especially 90%-97%.

[0011] According to another embodiment of the present invention, the collagen filler of the present invention has a dynamic viscosity of 90,000 to 300,000 mPa.s, preferably 95,000 to 280,000 mPa.s, even 98,000 to 270,000 mPa.s, especially 100,000 to 260,000 mPa.s, and particularly 120,000 to 250,000 mPa.s, at a shear rate of 2 Hz and a temperature of 25±1°C.

[0012] According to another embodiment of the present invention, the melting point of the collagen filler of the present invention is 55°C to 85°C, preferably 58°C to 80°C, even 60°C to 78°C, especially 62°C to 75°C, particularly greater than 65°C, or lower than 72°C.

[0013] According to another embodiment of the present invention, the cross-linking degree of the collagen filler of the present invention is 10% to 70%, preferably 12% to 65%, even 15% to 60%, especially 18% to 55%, and particularly 20% to 50%.

[0014] According to another embodiment of the present invention, the degradation loss rate of the collagen filler of the present invention under certain enzymatic hydrolysis conditions is less than 40%, preferably less than 35%, even less than 30%, especially less than 25%, and particularly less than 20%.

[0015] According to another embodiment of the present invention, the melting point of the collagen filler of the present invention is 55°C to 85°C, preferably 58°C to 80°C, even 60°C to 78°C, especially 62°C to 75°C, particularly greater than 65°C, or lower than 73°C.

[0016] According to another embodiment of the present invention, the collagen filler of the present invention comprises a combination of different pore sizes, preferably a combination of one or more pore sizes of 50 μm to 120 μm and one or more pore sizes of 120 μm to 500 μm, or even a combination of one or more pore sizes of 50 μm to 100 μm and one or more pore sizes of 120 μm to 450 μm, in particular a combination of one or more pore sizes of 50 μm to 90 μm and one or more pore sizes of 130 μm to 420 μm, or a combination of one or more pore sizes of 50 μm to 80 μm and one or more pore sizes of 140 μm to 400 μm.

[0017] According to another embodiment of the present invention, the collagen filler of the present invention has an average pore size D 50 The nanostructured carbon fiber has a thickness of 50 μm to 500 μm, a porosity of 80% to 99.5%, a cross-linking degree of 10% to 70%, and an in vitro enzymatic degradation loss rate of less than 40%.

[0018] The collagen filler of the present invention is prepared by a dynamic template method. On the one hand, the relative spacing of the collagen fiber bundles during the cross-linking process is controlled by controlling the pore size using microspheres as templates, thereby controlling the pore size after the collagen fiber bundles form a cross-linked skeleton; on the other hand, a dynamic single-template (or multi-template) cross-linking process is realized by controlling the mechanical stirring and microsphere addition method, so that each collagen fiber bundle can obtain the same cross-linking opportunity, thereby achieving a more thorough and uniform cross-linking effect of the collagen implant.

[0019] According to another embodiment of the present invention, the method for preparing a collagen filler of the present invention regulates the hierarchical porous structure inside the collagen filler by controlling the order of adding microspheres of different pore sizes during the template pore making process. For example, at the beginning of the cross-linking process, microspheres with large pores are first added for a period of cross-linking reaction, and then the microspheres with large pores are separated, and then microspheres with smaller pores are added as a pore making template to continue to participate in the cross-linking reaction, and the above steps are repeated according to the pore size required by the product, thereby preparing a fiber mesh hierarchical porous structure with large pores covering one or more small pores (or containing small pores). Generally, a pore size of 50 to 400 μm is conducive to cell migration and tissue ingrowth. Among them, the pore wall composed of cross-linked mesh fibers has higher mechanical properties, which is conducive to cell adhesion; the microporous structure of the through-holes covering small pores (or containing small pores) and the mesh fibers interweaving gives the collagen filler a higher porosity, which is conducive to the transportation of nutrients and the discharge of cell metabolic products, thereby providing more convenient spatial topological structures for tissue regeneration. The collagen filler prepared by the present invention can construct a pore structure suitable for tissue defects by adjusting the size, quantity, and step-by-step addition sequence of the pore-making template, thereby constructing a tissue filler that is more compatible with tissue repair and regeneration, and is convenient for different usage situations.

[0020] The collagen filler of the present invention prepared according to the method of the present invention may have a multi-level pore size, for example, a multi-level pore size of two or more combinations of a larger pore size and a smaller pore size in the range of 50 μm to 500 μm, for example, a multi-level pore size of two or more combinations of a smaller pore size of 50 μm to 120 μm and a larger pore size of 120 μm to 400 μm. The collagen filler of the invention with a multi-level pore size also exhibits excellent performance in mechanics, which is manifested as a higher dynamic viscosity. This may be due to the fact that the pores are connected by cross-linked collagen reticular fibers, so that it still maintains a high viscosity under the action of shear force, which greatly reduces the risk of displacement of the product after implantation into the tissue, and is more suitable for filling and repairing moderate to severe gravity wrinkles.

[0021] According to another embodiment of the present invention, the method for preparing the collagen filler of the present invention comprises the following steps:

[0022] (1) providing collagen, dissolving the collagen, and optionally filtering and sterilizing the collagen;

[0023] (2) adding a buffer solution, adjusting the pH to 6-8, and stirring to form a collagen suspension;

[0024] (3) Add microspheres and stir until uniform;

[0025] (4) adding a crosslinking agent, adjusting the temperature to 10-40° C., and carrying out a crosslinking reaction under constant temperature conditions;

[0026] (5) Removing microspheres from the suspension.

[0027] According to another embodiment of the present invention, in step (1), the concentration of the dissolved collagen solution is 0.5-15 mg / mL, preferably 0.8-12 mg / mL, even 1-10 mg / mL, especially 1.5-8 mg / mL, and particularly 2-6 mg / mL.

[0028] According to another embodiment of the present invention, in step (1), collagen is dissolved in 0.001-0.1 mol / L acid solution, such as an inorganic acid or an organic acid, particularly selected from hydrochloric acid, phosphoric acid, acetic acid, citric acid, or a mixture thereof.

[0029] According to another embodiment of the present invention, in step (1), the collagen is dissolved under stirring, for example, stirring for 1 h to 5 days, even 6 h to 4 days, especially 12 h to 3 days, and particularly 24 h to 2 days.

[0030] According to another embodiment of the present invention, in step (1), the temperature for dissolving collagen is 0°C to 25°C, even 1°C to 20°C, especially 2°C to 10°C, and particularly 4°C to 8°C.

[0031] According to another embodiment of the present invention, in step (2), the buffer solution is selected from phosphate buffer solution, such as phosphate / hydrogen phosphate buffer solution, citrate buffer solution, Tris buffer, potassium dihydrogen phosphate-sodium hydroxide buffer, disodium hydrogen phosphate-citric acid buffer.

[0032] According to another embodiment of the present invention, in step (2), the treatment temperature is 20°C to 37°C, even 25°C to 35°C, especially 27°C to 34°C, particularly 30°C to 33°C.

[0033] According to another embodiment of the present invention, in step (2), the concentration of the buffer solution is 0.05-0.5 mol / L, preferably 0.06-0.3 mol / L, particularly 0.08-0.25 mol / L, and especially 0.09-0.2 mol / L.

[0034] According to another embodiment of the present invention, in step (2), the volume ratio of the collagen solution to the buffer solution is 20:1 to 5:1, or even 15:1 to 6:1, particularly 12:1 to 7:1, and especially 10:1 to 8:1.

[0035] According to another embodiment of the present invention, in step (2), the pH is adjusted to 6.0 to 8.0, or even 6.5 to 7.5, especially 6.8 to 7.3, and particularly 6.9 to 7.2.

[0036] According to another embodiment of the present invention, the material of the microspheres is a biomedical inert material. Preferably, the microspheres are inert microspheres selected from inert bioceramic microspheres, medical metal and alloy microspheres, and inert polymer material microspheres, such as alumina ceramic microspheres, titanium alloy microspheres, polytetrafluoroethylene microspheres, alumina ceramic microspheres, titanium silicon microspheres, ArteFill (polymethyl methacrylate microspheres, PMMA), Radiance (hydroxyapatite microspheres, CaHA), Sculptra (poly L-lactic acid microspheres, PLLA), ELLANSE (polycaprolactone microspheres, PCL), etc.

[0037] According to another embodiment of the present invention, the average particle size of the microspheres is 50 μm to 500 μm, preferably 80 μm to 400 μm, even 90 μm to 300 μm, especially 100 μm to 250 μm, and particularly 120 μm to 200 μm. Optionally, according to the requirements, the steps (3) to (5) can be repeated multiple times, especially 2-5 times, or even 2 or 3 times, wherein the average particle size of the microspheres is different, wherein the particle size of the microspheres is different, preferably a combination of one or more particle sizes of 50 μm to 120 μm and one or more particle sizes of 120 μm to 500 μm, or even a combination of one or more particle sizes of 50 μm to 100 μm and one or more particle sizes of 120 μm to 450 μm, especially a combination of one or more particle sizes of 50 μm to 90 μm and one or more particle sizes of 130 μm to 420 μm, or a combination of one or more particle sizes of 50 μm to 80 μm and one or more particle sizes of 140 μm to 400 μm. Optionally, according to the filling requirements, one or more microspheres of different diameters can be added to the collagen suspension, and the pore formation effect of the collagen implant can be controlled by controlling the size of the microsphere diameter, thereby finally meeting the filling requirements of different facial depressions.

[0038] According to another embodiment of the present invention, the stacking volume of the microspheres is 0.1% to 10%, preferably 0.2% to 8%, even 0.3% to 6%, especially 0.4% to 5%, especially 0.5% to 4%, or 1-3% relative to the total volume of the collagen suspension. The stacking volume value of the microspheres directly determines the amount of porous structure of the collagen during the cross-linking process. That is, when the stacking volume of the microspheres accounts for a large proportion of the collagen suspension, it means that when the diameter of the microspheres is the same, a larger amount of microspheres added fills the collagen suspension with more microspheres, which causes more pores to appear in the cross-linked skeleton, thereby forming a larger cross-linked network.

[0039] According to another embodiment of the present invention, in step (3), the treatment temperature is 20°C to 37°C, even 25°C to 35°C, especially 27°C to 34°C, particularly 30°C to 33°C.

[0040] According to another embodiment of the present invention, in step (4), the cross-linking agent is any one or more of epoxide cross-linking agents, such as sorbitol, glycerol, and 1,4-butanediol diglycidyl ether.

[0041] According to another embodiment of the present invention, in step (4), the concentration of the crosslinking agent is 0.005%-3.0%, even 0.01%-2.0%, especially 0.015%-1.5%, particularly 0.02%-1.0%, or 0.025%-0.5%.

[0042] According to another embodiment of the present invention, in step (4), the pH is adjusted to 8 to 12, even 8.5 to 11.5, especially 9.0 to 11.0, and particularly 9.5 to 10.5.

[0043] According to another embodiment of the present invention, in step (4), the reaction temperature is 20-40°C, even 25°C to 37°C, especially 28°C to 36°C, particularly 30°C to 35°C.

[0044] According to another embodiment of the present invention, in step (4), the reaction time is 6 h to 8 days, even 12 h to 6 days, especially 36 h to 5 days, particularly 2 days to 4 days.

[0045] According to another embodiment of the present invention, in step (5), the microspheres are removed by sieving. For example, the specific operation may be to set a sieve at the outlet of the reaction tank, and sieve while stirring to prevent the microspheres from clogging the sieve. The sieve aperture is adjusted according to the specific size of the microspheres.

[0046] According to another embodiment of the present invention, in the purification step, the product is collected by centrifugation at a speed of >5000 rpm, and then repeatedly washed with 5-50 volumes of phosphate buffer for more than 5 times (including 5 times) to remove the cross-linking agent, wherein, for example, the concentration of the phosphate buffer is 0.05-0.3 mol / L, preferably 0.08-0.20 mol / L, especially 0.09-0.15 mol / L, and particularly 0.10-0.12 mol / L.

[0047] According to another embodiment of the present invention, in the purification step, the amount of phosphate buffer added each time is 6-10 times of the centrifugal precipitation, and the washing is greater than or equal to 5 times to remove the cross-linking agent in the cross-linked collagen suspension.

[0048] According to another embodiment of the present invention, the method of the present invention further comprises a homogenization step, wherein the product is poured into a homogenizer and homogenized until uniform, for example, the homogenization is cyclically performed for more than or equal to 2 times, or even more than or equal to 3 times.

[0049] According to another embodiment of the present invention, the method for preparing the collagen filler of the present invention further comprises a filling step, wherein the homogenized sample is filled into a syringe, and after inner packaging and outer packaging, the collagen filler is obtained.

[0050] According to another embodiment of the present invention, the preparation method of the collagen filler of the present invention is carried out in the following steps:

[0051] (1) Dissolving collagen extracted from tissue in a 0.001 mol / L to 0.1 mol / L acid solution, and then filtering and sterilizing;

[0052] (2) adding phosphate buffer solution, adjusting the pH to 6-8, and stirring at a certain temperature until collagen precipitates to form a white suspension;

[0053] (3) adding 0.1%-10% (v / v) microspheres and continuing to stir at a certain temperature until uniform;

[0054] (4) adding a cross-linking agent, adjusting the temperature to 20-40° C., and reacting for 3-10 days under constant temperature conditions;

[0055] (5) sieving the suspension while stirring, wherein the sieve aperture is changed according to the size of the microspheres (sieve aperture < microsphere diameter) to remove all the microspheres in the suspension;

[0056] (6) collecting the product by centrifugation and repeatedly washing with phosphate buffer to remove the cross-linking agent;

[0057] (7) Homogenization: Pour the product into a homogenizer and homogenize until uniform;

[0058] (8) Optionally, filling: filling the homogenized sample into a syringe, and obtaining a collagen filler after inner and outer packaging.

[0059] According to another embodiment of the present invention, the temperature of step (2) and step (3) is 20-40°C,

[0060] For example, 25-37℃.

[0061] The collagen described in the present invention is extracted from animals such as animal tissues and can be used for injection into the middle to deep layers of the dermis to fill skin defects caused by soft tissue defects.

[0062] According to another embodiment of the present invention, the collagen used to prepare the collagen filler of the present invention is collagen extracted from animal tissue, including one or more of bovine, equine, ovine, porcine, or fish atelocollagen type I, II, or III, collagen-rich decellularized human skin tissue, decellularized porcine skin tissue, or bovine skin tissue; more preferably, porcine atelocollagen type I or III.

[0063] According to another embodiment of the present invention, the collagen used to prepare the collagen filler of the present invention is a modified collagen obtained by chemical cross-linking. In an in vitro enzymatic hydrolysis test, for example, at 37°C and a collagenase concentration of 1 mg / ml, after a certain period of enzymatic hydrolysis, the degree of enzymatic hydrolysis is no more than 40%.

[0064] According to another embodiment of the present invention, the collagen used to prepare the collagen filler of the present invention is a modified collagen obtained by chemical cross-linking. After the cross-linking process is completed, it will be cleaned to remove the cross-linking agent that has not participated in the reaction to ensure the safety of the collagen filler. The residual amount of cross-linking agent in the collagen filler prepared by the present invention was detected by gas chromatography, and the result was not detected. And it is much lower than the control amount of other facial fillers for this indicator (≤2.0μg / g).

[0065] In order to achieve the purpose of the present invention, the present invention adopts a dynamic template method to prepare a collagen filler. On the one hand, by controlling the pore size of the microsphere as a template, the relative spacing of the collagen fiber bundles during the cross-linking process is controlled, thereby controlling the size of the pores after the collagen fiber bundles form a cross-linked skeleton; on the other hand, by controlling a certain stirring speed, each collagen fiber bundle can obtain the same cross-linking opportunity under dynamic conditions, thereby achieving a more thorough and uniform cross-linking effect of the collagen implant.

[0066] The collagen filler provided by the present invention has a macroporous fiber network structure. Due to a more complete cross-linking reaction, the "skeleton" composed of the fibers has a higher dynamic viscosity and exhibits stronger mechanical properties.

[0067] The collagen filler of the present invention obtains a fiber mesh structure with controllable pore size by adopting a dynamic template method, and then obtains collagen fibers with more complete cross-linking reaction by reducing the concentration of the cross-linking agent and prolonging the cross-linking time, thereby improving the filler's resistance to enzymatic hydrolysis. In view of the fact that a fiber mesh structure with controllable pore size is obtained, on the one hand, microsphere templates of different diameters can be used to prepare implant samples with different pore sizes, and implants with different pore sizes can be adapted to fill skin with different degrees of depression; on the other hand, the fully reacted cross-linking sites also obtain a longer maintenance time, which is conducive to the product obtaining a more lasting and stable filling effect after implantation.

[0068] In addition, the collagen filler provided by the present invention adopts a template method to build a collagen fiber network during the process of cross-linking collagen fibers, so the implant retains more fiber reticular structures, ensures the transportation of nutrients and metabolites after implantation in the body, and induces cells to migrate, proliferate and differentiate into the implant, thereby causing local fibroblasts to proliferate and synthesize and secrete more type I collagen fibers.

[0069] The collagen filler provided by the present invention retains a portion of the intact triple helix structure of collagen, thereby retaining the active ingredients of collagen and greatly reducing the potential sensitization and toxicity risks of cross-linking reactions.

[0070] The present invention also relates to a collagen composition, comprising the collagen filler of the present invention, optionally comprising additives, such as suspending agents, antioxidants, therapeutic active agents such as pharmaceutical active agents; comprising nutrients, proteins such as recombinant collagen, polypeptides, various amino acids, polysaccharides such as sodium hyaluronate, chitosan; or combinations thereof.

[0071] The present invention also relates to the use of the collagen filler of the present invention in the preparation of medical plastic surgery products such as treatment of fine lines, facial sculpture, correction, surgical operations or surgical treatment fillers.

[0072] The present invention also relates to a method for medical plastic surgery, such as treatment of fine lines, facial sculpting, correction, surgery or surgical treatment, which comprises the step of using the collagen filler according to the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0073] Figure 1 The scanning electron microscope image of the freeze-dried product of the collagen filler of Example 1 of the present application is shown. The collagen filler of the present invention has a hierarchical porous structure.

[0074] Figure 2 The scanning electron micrograph of the freeze-dried product of the collagen filler of Comparative Example 1 of the present application is shown.

[0075] Figure 3 The gas chromatogram of the cross-linking agent residue in the collagen filler of Example 4 of the present application is shown (not detected).

[0076] Figure 4 The scanning electron micrograph of the freeze-dried product of the collagen filler of Example 6 of the present application is shown. DETAILED DESCRIPTION

[0077] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Therefore, the detailed description of the embodiments of the present invention provided below does not limit the scope of the claimed invention, but only represents the selected embodiments of the present invention.

[0078] Examples 1-6 and Comparative Examples 1-3: Preparation of collagen fillers

[0079] Embodiment 1:

[0080] Embodiment 1 of the present invention implements the following steps:

[0081] (1) Dissolving collagen solution: Weigh 10 g of collagen, the collagen raw material is purchased type I collagen (Guangdong Shengchi, GVB-atelo-03), sourced from pigs. Add 2000 mL of 0.01 mol / L hydrochloric acid solution, stir at 4°C for 48 h until completely dissolved, and obtain a uniform collagen solution;

[0082] Filtration sterilization: Under a pressure of 0.25Mpa, the collagen solution is filtered using a 0.2μm filter membrane, and filtered twice to achieve the purpose of sterilization to obtain a sterile collagen filtrate.

[0083] (2) Collagen fiber precipitation: Add 0.1 mol / L phosphate alkaline (0.1 mol / L NaOH) buffer solution, adjust the pH to 6, and stir at room temperature until collagen fibers are precipitated.

[0084] (3) Template pore making: Alumina ceramic microspheres with diameters of 50 μm and 100 μm were added, with the stacking volume proportions being 0.5% and 1%, respectively, and the mixture was stirred at 25° C. until uniform.

[0085] (4) Cross-linking: Add 0.01 mol / L phosphate alkaline (0.1 mol / L NaOH) buffer solution containing 4 g of sorbitol, adjust the pH to 11, adjust the temperature to 30° C., and stir the reaction for 3 days.

[0086] (5) Sieving: The suspension is sieved while being stirred, wherein the mesh size of the sieve is 320 meshes to remove all the microspheres in the suspension;

[0087] (6) Purification: The product was collected by centrifugation at 5000 rpm, and the collagen suspension was repeatedly washed with 10 volumes of 0.01 mol / L sterile phosphate buffer. The above operation was repeated 5 times to remove the cross-linking agent residues and bacterial endotoxins in the collagen.

[0088] (7) Homogenization: Pour the purified collected product into a homogenizer and homogenize three times until uniform;

[0089] (8) Filling: The homogenized sample is filled into a 1 mL syringe, and then the collagen filler is obtained after inner and outer packaging.

[0090] Embodiment 2:

[0091] Embodiment 2 of the present invention implements the following steps:

[0092] (1) Dissolving collagen solution: Weigh 10 g of collagen, the collagen raw material is purchased type I collagen, sourced from pigs. Add 2000 mL of 0.01 mol / L hydrochloric acid solution, stir at 10°C for 30 h until completely dissolved, and obtain a uniform collagen solution;

[0093] Filtration sterilization: Under a pressure of 0.25Mpa, the collagen solution was filtered using a 0.2μm filter membrane, and filtered twice to achieve the purpose of sterilization to obtain a sterile collagen filtrate.

[0094] (2) Collagen fiber precipitation: add 0.1 mol / L phosphate alkaline (0.1 mol / L NaOH) buffer solution to adjust the pH to 6, and stir at room temperature until collagen fibers are precipitated.

[0095] (3) Template pore making: Add alumina ceramic microspheres with a diameter of 100 μm, with a stacking volume ratio of 1%, and continue stirring at 25° C. until uniform.

[0096] (4) Cross-linking: Add 0.01 mol / L phosphate alkaline (0.1 mol / L NaOH) buffer solution containing 6 g of sorbitol, adjust the pH to 11, adjust the temperature to 35° C., and stir the reaction for 6 days.

[0097] (5) Sieving: The suspension is sieved while being stirred, wherein the mesh size of the sieve is 160 meshes to remove all the microspheres in the suspension;

[0098] (6) Purification: The product was collected by centrifugation at 5000 rpm, and the collagen suspension was repeatedly washed with 10 volumes of 0.01 mol / L sterile phosphate buffer. The above operation was repeated 5 times to remove the cross-linking agent residues and bacterial endotoxins in the collagen.

[0099] (7) Homogenization: Pour the purified collected product into a homogenizer and homogenize three times until uniform;

[0100] (8) Filling: The homogenized sample is filled into a 1 mL syringe, and then the collagen filler is obtained after inner and outer packaging.

[0101] Embodiment 3:

[0102] Embodiment 3 of the present invention implements the following steps:

[0103] (1) Dissolving collagen solution: Weigh 10 g of collagen, the collagen raw material is type I collagen purchased by our company, sourced from pigs. Add 2000 mL of 0.01 mol / L hydrochloric acid solution, stir at 10°C for 30 h until completely dissolved, and obtain a uniform collagen solution;

[0104] Filtration sterilization: Under a pressure of 0.25Mpa, the collagen solution was filtered using a 0.2μm filter membrane, and filtered twice to achieve the purpose of sterilization to obtain a sterile collagen filtrate.

[0105] (2) Collagen precipitation: Add 0.1 mol / L phosphate alkaline (0.1 mol / L NaOH) buffer solution to the sterile collagen filtrate obtained in step (2), adjust the pH to 7, and stir at room temperature until collagen fibers are precipitated.

[0106] (3) Template pore making: Add polytetrafluoroethylene microspheres with a diameter of 100 μm, with a stacking volume ratio of 2%, and continue stirring at 25° C. until uniform.

[0107] (4) Cross-linking: Add 0.01 mol / L phosphate alkaline (0.1 mol / L NaOH) buffer solution containing 6 g of sorbitol, adjust the pH to 11, adjust the temperature to 35° C., and stir the reaction for 6 days.

[0108] (5) Sieving: The suspension is sieved while being stirred, wherein the mesh size of the sieve is 160 meshes to remove all the microspheres in the suspension;

[0109] (6) Purification: The product was collected by centrifugation at 6000 rpm, and the collagen suspension was repeatedly washed with 8 volumes of 0.01 mol / L sterile phosphate buffer. The above operation was repeated 6 times to remove the cross-linking agent residues and bacterial endotoxins in the collagen.

[0110] (7) Homogenization: Pour the purified collected product into a homogenizer and circulate homogenization 3 times until uniform;

[0111] (8) Filling: The homogenized sample is filled into a 1 mL syringe, and then the collagen filler is obtained after inner and outer packaging.

[0112] Embodiment 4:

[0113] Embodiment 4 of the present invention implements the following steps:

[0114] (1) Dissolving collagen solution: Weigh 10 g of collagen, the collagen raw material is type I collagen purchased by our company, sourced from pigs. Add 4000 mL of 0.01 mol / L hydrochloric acid solution, stir at 10°C for 18 h until completely dissolved, and obtain a uniform collagen solution;

[0115] Filtration sterilization: Under a pressure of 0.2Mpa, the collagen solution is filtered using a 0.2μm filter membrane, and filtered twice to achieve the purpose of sterilization to obtain a sterile collagen filtrate.

[0116] (2) Collagen precipitation: Add 0.1 mol / L alkaline (0.1 mol / L NaOH) phosphate buffer solution to the sterile collagen filtrate obtained in step (2), adjust the pH to 7, and stir at room temperature until collagen fibers are precipitated.

[0117] (3) Template pore making: Add polytetrafluoroethylene microspheres with a diameter of 200 μm, with a stacking volume ratio of 2%, and continue stirring at 25°C until uniform.

[0118] (4) Cross-linking: Add 0.01 mol / L phosphate alkaline (0.1 mol / L NaOH) buffer solution containing 6 g of 1,4-butanediol glycidyl ether (purity ≥ 95%), adjust the pH to 9, adjust the temperature to 30° C., and stir the reaction for 3 days.

[0119] (5) Sieving: The suspension is sieved while being stirred, wherein the mesh size of the sieve is 90 meshes to remove all the microspheres in the suspension;

[0120] (6) Purification: The product was collected by centrifugation at a speed of 10,000 rpm, and the collagen suspension was repeatedly washed with 8 volumes of 0.01 mol / L sterile phosphate buffer. The above operation was repeated 6 times to remove the cross-linking agent residues and bacterial endotoxins in the collagen.

[0121] (7) Homogenization: Pour the purified collected product into a homogenizer and circulate homogenization for 3 times until uniform.

[0122] (8) Filling: The homogenized sample is filled into a 1 mL syringe, and then the collagen filler is obtained after inner and outer packaging.

[0123] Embodiment 5:

[0124] Embodiment 5 of the present invention implements the following steps:

[0125] (1) Dissolving collagen solution: Weigh 10 g of collagen, the collagen raw material is type I collagen purchased by our company, sourced from pigs. Add 3000 mL of 0.01 mol / L hydrochloric acid solution, stir at 10°C for 16 h until completely dissolved, and obtain a uniform collagen solution;

[0126] Filtration sterilization: Under a pressure of 0.25Mpa, the collagen solution was filtered using a 0.2μm filter membrane, and filtered twice to achieve the purpose of sterilization to obtain a sterile collagen filtrate.

[0127] (2) Collagen precipitation: Add 0.1 mol / L phosphate alkaline (0.1 mol / L NaOH) buffer solution to the sterile collagen filtrate obtained in step (2), adjust the pH to 8, and stir at room temperature until collagen fibers are precipitated.

[0128] (3) Template pore making: Add polytetrafluoroethylene microspheres with a diameter of 200 μm, with a stacking volume ratio of 1%, and continue stirring at room temperature until uniform.

[0129] (4) Cross-linking: Add 0.01 mol / L phosphate alkaline (0.1 mol / L NaOH) buffer solution containing 6 g of 1,4-butanediol glycidyl ether (purity ≥ 95%), adjust the pH to 9, adjust the temperature to 30° C., and stir the reaction for 3 days.

[0130] (5) Sieving: The suspension is sieved while being stirred, wherein the mesh size of the sieve is 90 meshes to remove all the microspheres in the suspension;

[0131] (6) Purification: The product was collected by centrifugation at a speed of 10,000 rpm, and the collagen suspension was repeatedly washed with 10 volumes of 0.01 mol / L sterile phosphate buffer. The above operation was repeated 5 times to remove the cross-linking agent residues and bacterial endotoxins in the collagen.

[0132] (7) Homogenization: Pour the purified collected product into a homogenizer and circulate homogenization 3 times until uniform;

[0133] (8) Filling: The homogenized sample is filled into a 1 mL syringe, and then the collagen filler is obtained after inner and outer packaging.

[0134] Embodiment 6:

[0135] Embodiment 6 of the present invention implements the following steps:

[0136] (1) Dissolving collagen solution: Weigh 10 g of collagen, the collagen raw material is type I collagen purchased by our company, sourced from pigs. Add 3000 mL of 0.01 mol / L hydrochloric acid solution, stir at 10°C for 16 h until completely dissolved, and obtain a uniform collagen solution;

[0137] Filtration sterilization: Filter the collagen solution using a 0.2 μm filter membrane at a pressure of 0.25 MPa.

[0138] (2) Filter twice to achieve the purpose of sterilization and obtain sterile collagen filtrate.

[0139] Collagen precipitation: add 0.1 mol / L phosphate alkaline (0.1 mol / L NaOH) buffer solution to the sterile collagen filtrate obtained in step (2), adjust the pH to 8, and stir at room temperature until collagen fibers are precipitated.

[0140] (3.1) First template pore making: Add polytetrafluoroethylene microspheres with a diameter of 200 μm, with a stacking volume ratio of 0.5%, and continue stirring at room temperature until uniform;

[0141] (4.1) Cross-linking: Add 0.01 mol / L phosphate alkaline (0.1 mol / L NaOH) buffer solution containing 6 g of 1,4-butanediol glycidyl ether (purity ≥ 95%), adjust the pH to 9, adjust the temperature to 35° C., and stir the reaction for 2 days.

[0142] (5.1) Sieving: The suspension is sieved while being stirred, wherein the mesh size of the sieve is 90 meshes to remove all the microspheres in the suspension;

[0143] (3.2) Second template pore making: Add polytetrafluoroethylene microspheres with a diameter of 50 μm, with a stacking volume ratio of 0.5%, and continue stirring at room temperature until uniform;

[0144] (4.2) Cross-linking: The cross-linking temperature was adjusted to 35°C and the reaction was stirred for 2 days.

[0145] (5.2) Sieving: The suspension is sieved while being stirred, wherein the mesh size of the sieve is 320 meshes to remove all the microspheres in the suspension;

[0146] (6) Purification: The product was collected by centrifugation at a speed of 10,000 rpm, and the collagen suspension was repeatedly washed with 10 volumes of 0.01 mol / L sterile phosphate buffer. The above operation was repeated 5 times to remove the cross-linking agent residues and bacterial endotoxins in the collagen.

[0147] (7) Homogenization: Pour the purified collected product into a homogenizer and circulate homogenization 3 times until uniform;

[0148] (8) Filling: The homogenized sample is filled into a 1 mL syringe, and then the collagen filler is obtained after inner and outer packaging.

[0149] Comparative Example 1: The steps are the same as those in Example 1, except that the triple cross-linking method is used and the template microspheres are not used for preparation. The following steps are performed:

[0150] (1) Dissolving collagen solution: Weigh 10 g of collagen, the collagen raw material is purchased type I collagen (Guangdong Shengchi, GVB-atelo-03), sourced from pigs. Add 2000 mL of 0.01 mol / L hydrochloric acid solution, stir at 4°C for 48 h until completely dissolved, and obtain a uniform collagen solution;

[0151] Filtration sterilization: Filter the collagen solution using a 0.2μm filter membrane under a pressure of 0.25Mpa, and filter twice to achieve the purpose of sterilization to obtain a sterile collagen filtrate.

[0152] (2) Collagen fiber precipitation: Add 0.1 mol / L phosphate alkaline (0.1 mol / L NaOH) buffer solution, adjust the pH to 6, and stir at room temperature until collagen fibers precipitate.

[0153] (3) First cross-linking: Add 0.01 mol / L phosphate alkaline (0.1 mol / L NaOH) buffer solution containing 0.3 g glutaraldehyde, adjust the pH to 7, adjust the temperature to 30°C, and stir the reaction for 16 hours.

[0154] (4) collecting the precipitate by centrifugation to obtain the cross-linked collagen fibers after the first cross-linking, and dispersing them in a phosphate buffer solution.

[0155] (5) Second cross-linking: Add 0.01 mol / L phosphate alkaline (0.1 mol / L NaOH) buffer solution containing 5 g of 1,4-butanediol diglycidyl ether to the obtained cross-linked collagen fibers, adjust the pH to 11, adjust the temperature to 40°C, and stir the reaction for 16 hours.

[0156] (6) collecting the precipitate by centrifugation to obtain the cross-linked collagen fibers after the second cross-linking, and dispersing them in a phosphate buffer solution.

[0157] (7) Third cross-linking: Add 0.01 mol / L phosphate alkaline (0.1 mol / L NaOH) buffer solution containing 5 g of carbodiimide to the obtained cross-linked collagen fibers, adjust the pH to 5, adjust the temperature to 35°C, and stir the reaction for 16 hours.

[0158] (8) collecting the precipitate by centrifugation to obtain the cross-linked collagen fibers after the third cross-linking.

[0159] (9) Purification: The product was collected by centrifugation at a speed of 5000 rpm to obtain the cross-linked collagen fibers after the third cross-linking. The fibers were washed repeatedly with 10 volumes of 0.01 mol / L sterile phosphate buffer. The above operation was repeated 5 times to remove the cross-linking agent residues and bacterial endotoxins in the collagen.

[0160] (10) Homogenization: Pour the purified collected product into a homogenizer and homogenize it three times until it is uniform;

[0161] (11) Filling: The homogenized sample is filled into a 1 mL syringe, and then the collagen filler is obtained after inner and outer packaging.

[0162] according to Figure 1 After the collagen filler of the present invention is freeze-dried to remove water, it presents a graded porous structure of 50-300 μm, and the pore walls are fibrous mesh pore walls formed by cross-linked collagen fibers.

[0163] The collagen filler in Example 1 and the collagen filler in Comparative Example 1 (such as Figure 2Compared with the above materials, the hierarchical porous structure has larger and richer pores. After the material is implanted into the human body, it is conducive to the growth of fibroblasts and the delivery of nutrients and metabolites to promote the regeneration and remodeling of the collagen fiber network. Figure 3 No cross-linking agent residue was detected in the collagen filler of the present invention, showing a residual amount of 0, indicating that the preparation process involved in the present invention removes the cross-linking agent more thoroughly, further confirming that the collagen filler of the present invention has high safety.

[0164] Comparative Example 2: The steps are the same as those in Example 1, except that Comparative Example 2 is prepared by a double cross-linking method and does not use template microspheres, and the following steps are performed:

[0165] (1) Dissolving collagen solution: Weigh 10 g of collagen, the collagen raw material is purchased type I collagen (Guangdong Shengchi, GVB-atelo-03), sourced from pigs. Add 2000 mL of 0.01 mol / L hydrochloric acid solution, stir at 4°C for 48 h until completely dissolved, and obtain a uniform collagen solution;

[0166] Filtration sterilization: Filter the collagen solution using a 0.2μm filter membrane under a pressure of 0.25Mpa, and filter twice to achieve the purpose of sterilization to obtain a sterile collagen filtrate.

[0167] (2) Collagen fiber precipitation: Add 0.1 mol / L phosphate alkaline (0.1 mol / L NaOH) buffer solution, adjust the pH to 6, and stir at room temperature until collagen fibers precipitate.

[0168] (3) First cross-linking: Add 0.01 mol / L phosphate alkaline (0.1 mol / L NaOH) buffer solution containing 20 g glucose, adjust the pH to 7, adjust the temperature to 30°C, and stir the reaction for 7 days.

[0169] (4) collecting the precipitate by centrifugation to obtain the cross-linked collagen fibers after the first cross-linking, and dispersing them in a phosphate buffer solution.

[0170] (5) Second cross-linking: Add 0.01 mol / L phosphate alkaline (0.1 mol / L NaOH) buffer solution containing 10 g carbodiimide and 2 g N-hydroxysuccinimide (NHS) to the obtained cross-linked collagen fibers, adjust the pH to 5.5, adjust the temperature to room temperature, and stir the reaction for 16 h.

[0171] (6) Purification: The product was collected by centrifugation at a speed of 5000 rpm to obtain the cross-linked collagen fibers after the second cross-linking. The fibers were washed repeatedly with 10 volumes of 0.01 mol / L sterile phosphate buffer. The above operation was repeated 5 times to remove the cross-linking agent residues and bacterial endotoxins in the collagen.

[0172] (7) Homogenization: Pour the purified collected product into a homogenizer and homogenize three times until uniform;

[0173] (8) Filling: The homogenized sample is filled into a 1 mL syringe, and then the collagen filler is obtained after inner and outer packaging.

[0174] Comparative Example 3: The steps are the same as those in Example 1, except that Comparative Example 3 is prepared by a method without using template microspheres, and the following steps are performed:

[0175] (1) Dissolving collagen solution: Weigh 10 g of collagen, the collagen raw material is purchased type I collagen (Guangdong Shengchi, GVB-atelo-03), sourced from pigs. Add 2000 mL of 0.01 mol / L hydrochloric acid solution, stir at 4°C for 48 h until completely dissolved, and obtain a uniform collagen solution;

[0176] Filtration sterilization: Filter the collagen solution using a 0.2μm filter membrane under a pressure of 0.25Mpa, and filter twice to achieve the purpose of sterilization to obtain a sterile collagen filtrate.

[0177] (2) Collagen fiber precipitation: Add 0.1 mol / L phosphate alkaline (0.1 mol / L NaOH) buffer solution, adjust the pH to 6, and stir at room temperature until collagen fibers precipitate.

[0178] (3) Cross-linking: Add 0.01 mol / L phosphate alkaline (0.1 mol / L NaOH) buffer solution containing 4 g sorbitol, adjust the pH to 11, adjust the temperature to 30°C, and stir the reaction for 3 days.

[0179] (4) Purification: The product was collected by centrifugation at 5000 rpm, and the collagen suspension was repeatedly washed with 10 volumes of 0.01 mol / L sterile phosphate buffer. The above operation was repeated 5 times to remove the cross-linking agent residues and bacterial endotoxins in the collagen;

[0180] (5) Homogenization: Pour the purified collected product into a homogenizer and homogenize it three times until it is uniform;

[0181] (6) Filling: The homogenized sample is filled into a 1 mL syringe, and then the collagen filler is obtained after inner and outer packaging.

[0182] Examples 7-10: Collagen filler properties results

[0183] Example 7: Dynamic viscosity of collagen filler

[0184] In this example, the dynamic viscosity of the collagen filler is tested.

[0185] Detection method: This experiment was conducted in accordance with the third method of the Pharmacopoeia of the People's Republic of China (Part II) (2020 edition), and the specific test parameters were carried out in accordance with "YY 0954-2015 Passive Surgical Implant Type I Collagen Implant". The test samples were Examples 1-6 and Comparative Examples 1-3.

[0186] Table 1 Dynamic viscosity test results of collagen fillers

[0187]

[0188] From the dynamic viscosity test data in Table 1 above, the dynamic viscosity of the collagen fillers of Examples 1-6 of the present invention is significantly higher than that of Comparative Examples 1-3. Without wishing to be bound by theory, the reasons may include the following two points: First, the collagen filler prepared by the dynamic template method has a larger pore size, which is manifested as a larger strain range. Second, after sufficient cross-linking reaction, its cross-linking sites improve the overall stability of the reticular fibers. The combined effect of the above two points enables the collagen filler in the present invention to exhibit a higher dynamic viscosity when resisting continuous shear force, indicating that it has better plasticity.

[0189] Example 8: Degree of cross-linking of collagen fillers

[0190] This example tests the cross-linking degree (amino substitution degree) of the collagen filler.

[0191] Detection method: In this experimental example, ninhydrin was used to detect the protein content to analyze the cross-linking degree of the collagen filler.

[0192] <Experimental Group 1>

[0193] Weigh 1.0 g of the samples prepared in Examples 1-6 respectively, add 3 mL of purified water and 2 mL of ninhydrin reaction solution, mix well, heat at 100° C. for 30 min, cool to room temperature in an ice water bath, then add 50% isopropanol to dilute to 25 mL, and measure the absorbance at 570 nm.

[0194] <Experimental Group 2>

[0195] The steps of Experimental Group 2 were the same as those of Experimental 1, except that the samples used in Experimental Group 2 were collagen implants prepared from uncrosslinked samples with the same concentration.

[0196] <Control group>

[0197] The procedures of the control group were the same as those of the experimental group 1, except that an equal amount of purified water was used to replace the test sample.

[0198] <Standard curve drawing>

[0199] L-glutamic acid was used as the standard solution to draw a standard curve. Specifically, 0, 0.2, 0.4, 0.6, 0.8, and 1.0 mL of 10 mmol / L L-glutamic acid standard solution were respectively drawn into a 25 mL stoppered colorimetric tube (the corresponding L-glutamic acid was 0, 2.0, 4.0, 6.0, 8.0, and 10.0 mmol, respectively), and then 1.0, 0.8, 0.6, 0.4, 0.2, and 0 mL of purified water were added in sequence, and the following operations were performed from "3 mL of purified water was added successively" in the above experimental group 1 until the detection was completed.

[0200] Crosslinking degree calculation formula:

[0201]

[0202] Wherein, a is the amount of amino groups corresponding to the absorbance value of the experimental group 1 minus the absorbance value of the control group, and b is the amount of amino groups corresponding to the absorbance value of the experimental group 2 minus the absorbance value of the control group.

[0203] Table 2 Cross-linking degree test results of collagen fillers

[0204] Degree of crosslinking Example 1 20.04% Example 2 43.76% Example 3 49.22% Example 4 24.70% Example 5 30.26% Example 6 21.36% Comparative Example 1 75.62% Comparative Example 2 62.30% Comparative Example 3 54.16%

[0205] According to the cross-linking degree test data in Table 2 above, the cross-linking degree of the collagen filler prepared by the method of Examples 1-6 of the present invention is significantly lower than that of the comparative example. The reason may be that the cross-linking reaction of the collagen fibers prepared by the method of the present invention mostly occurs on the surface of the collagen fiber bundles, and some natural collagen fibers are still retained inside, which is crucial to maintaining the activity of collagen.

[0206] Example 9: Degree of enzymatic hydrolysis of collagen filler

[0207] This example detects the degree of enzymatic hydrolysis of the collagen filler.

[0208] Detection method: This experimental example reflects the degree of enzymatic hydrolysis of the test sample in a certain period of time by detecting the ratio of the hydroxyproline content in the supernatant of the test sample after enzymatic hydrolysis to the hydroxyproline content in the test sample without enzymatic hydrolysis.

[0209] The hydroxyproline content in the supernatant of the enzymatic hydrolysis of the test sample and the hydroxyproline content in the test sample without enzymatic hydrolysis were detected according to Appendix B of YY / T 1151-2017 Collagen Sponge.

[0210] The enzymatic treatment of the samples was as follows:

[0211] <Experimental Group 1>

[0212] Weigh 1.0 g of the samples prepared in Examples 1-6 and the comparative example, add 9 mL of collagenase solution (pH 7.4, phosphate buffer solution containing 0.1 mmol / L CaCl2, collagenase concentration of 1 mg / mL), mix well, and incubate in a 37°C water bath for 2 h. After centrifugation, take 1 mL of the supernatant for hydroxyproline content detection.

[0213] <Experimental Group 2>

[0214] 1.0 g of the samples prepared in Examples 1-6 were weighed respectively and tested according to Appendix B of YY / T 1151-2017 Collagen Sponge.

[0215] <Control group>

[0216] The procedures of the control group were the same as those of the experimental group 1, except that an equal amount of purified water was used to replace the test sample.

[0217] Crosslinking degree calculation formula:

[0218]

[0219] Among them, A is the hydroxyproline content corresponding to the absorbance value of the experimental group 1 minus the absorbance value of the control group, and B is the hydroxyproline content corresponding to the absorbance value of the experimental group 2 minus the absorbance value of the control group.

[0220] Table 3 Results of enzymatic hydrolysis test of collagen fillers

[0221] Degree of enzymatic hydrolysis Example 1 39.25% Example 2 18.00% Example 3 36.10% Example 4 38.45% Example 5 32.66% Example 6 20.67% Comparative Example 1 46.49% Comparative Example 2 48.67% Comparative Example 3 54.18%

[0222] According to the enzymatic hydrolysis degree detection data in Table 3 above, the enzymatic hydrolysis degree of the collagen filler obtained by the method of Examples 1-6 of the present invention is significantly lower than the result measured in the comparative example. The main reason is that the cross-linking reaction in the present invention adopts epoxide, and its cross-linking reaction rate with collagen is slower than glutaraldehyde, which provides more sufficient reaction conditions for the active groups on the surface of the collagen fibers, so that the cross-linking reaction in the entire collagen fiber is evenly distributed and complete. In addition, on the one hand, by adjusting the reaction temperature, cross-linking agent concentration and reaction pH, the sufficient degree of collagen cross-linking reaction can be improved, so that the sample can still maintain a low degree of enzymatic hydrolysis at a low degree of cross-linking; on the other hand, by adjusting the diameter size and stacking volume ratio of the dynamic template, the cross-linked network structure is adjusted to obtain collagen fillers with different void structures, so that the sample has more application scenarios.

[0223] Example 10: Average pore size and porosity of collagen filler

[0224] Under the same conditions, each test sample was injected into the same cylindrical mold and freeze-dried.

[0225] (1) Average pore size: Take a midline cross section of the sample and place it horizontally on one side of the cross-section sample stage. Observe it using a scanning electron microscope, count the pore sizes, and calculate the average value.

[0226] (2) Porosity: The porosity of the sample (after drying) was measured by the pycnometer method, specifically, as follows:

[0227] Under constant temperature conditions, an accurately weighed sample (Ws) is immersed in a pycnometer filled with ethanol, which is pre-weighed as W1. A vacuum is applied to degas the sample until the sample is completely saturated with ethanol, and then the pycnometer is refilled with ethanol and the total weight of the system is recorded as W2. The sample with ethanol is then removed and the weight of the pycnometer and the total weight of the ethanol remaining in the pycnometer are recorded as W3. Therefore, the porosity (ε) of the sample under test is calculated as follows:

[0228] ε=VP / (Vp+Vs)=(W2-W3-Ws) / (W1-W3)

[0229] Where Vs is the volume of the sample (excluding internal pores), and Vp is the pore volume inside the sample.

[0230] (3) Cell proliferation assay: CCK-8 was used to detect the relative number of cells during proliferation.

[0231] The specific steps are as follows:

[0232] a) Inject 0.1 g of the test sample into a 48-well plate and take the cell suspension at 5×10 3 / well density of rBMSCs were seeded on the surface of the test article, and the TCPS group was used as the control group. The culture plate was transferred to the incubator. After the cells attached for 2 hours, 500 μL of α-MEM culture medium was added to each well and the plate was placed in the incubator for further culture. The medium was changed every other day, and the day of cell seeding was recorded as day 0 of cell growth.

[0233] b) Preparation of CCK-8 solution: CCK-8 liquid and culture medium are prepared at a volume ratio of 1:9 to obtain CCK-8 solution;

[0234] c) After the cells were cultured in contact culture for 1, 3, 5, and 7 days, the culture medium was aspirated, 200 μL of CCK-8 solution was added to each well, and the cells were placed in an incubator and incubated for 2 h;

[0235] d) Take out the culture plate after incubation, take 100 μL of the solution and place it on an ELISA plate, select a wavelength of 450 nm for quantitative detection of absorbance, record the value, and calculate the cell proliferation rate.

[0236] Table 4 Results of average pore size, porosity and cell growth rate

[0237]

[0238] According to the results of the average pore size and porosity in Table 4 above, the samples prepared by the methods of Examples 1-6 all showed a higher average pore size and a higher porosity. Example 6 obtained a hierarchical porous structure and a higher porosity. In Example 6, the prepared collagen filler was added successively by controlling the microspheres with large (200 μm) and small (50 μm) pore sizes, and the final prepared collagen filler had a higher dynamic viscosity, porosity, a suitable porous structure, and a lower degree of cross-linking and enzymatic hydrolysis, which is more suitable for filling and repairing moderate to severe gravity wrinkles. As shown in Table 4, the collagen filler of Example 6 of the present invention has a higher cell growth rate. Moreover, the cell survival rate of the collagen filler prepared by the methods of Examples 1-6 is significantly higher than that of Comparative Example 1, Comparative Example 2, Comparative Example 3 and the negative control example, indicating that the sample prepared by the invention is non-cytotoxic and exhibits better cell compatibility.

[0239] Example 11: In vitro cytotoxicity of collagen

[0240] This example detects the in vitro cytotoxicity of collagen fillers.

[0241] Detection method: This experiment was carried out according to the test method in GB / T 16886.5-2017 "Biological evaluation of medical devices: Part 5: In vitro cytotoxicity test".

[0242] Table 6 In vitro cytotoxicity test results of collagen fillers

[0243] In vitro cytotoxicity test results (cell survival rate) Example 1 114.49±4.29% Example 2 110.86±6.57% Example 3 108.79±4.13% Example 4 118.36±10.65% Example 5 111.86±9.78% Example 6 115.63±4.26% Comparative Example 1 97.31±3.65% Comparative Example 2 96.32±1.49% Comparative Example 3 98.45±3.67% Blank control example 100% Positive control example 7.31±2.46% Negative control example 98.61±1.68%

[0244] According to the results of the in vitro cytotoxicity test in Table 6 above, the samples prepared by the above methods all showed a high cell survival rate. Among them, the cell survival rate of the collagen filler prepared by the methods of Examples 1-6 was significantly higher than that of Comparative Examples 1, 2, 3 and the negative control example, indicating that the samples prepared by the invention were non-cytotoxic and showed better cell compatibility.

[0245] In summary, the collagen filler prepared by the present invention has a fiber porous scaffold that can simulate the natural extracellular matrix in structure, and partially retains the most characteristic triple helix structure of the collagen molecule. Through a sufficient and complete cross-linking reaction, a collagen filler with significantly improved mechanical properties and greatly reduced enzymatic hydrolysis is obtained, which is conducive to prolonging the action time of the filler in the tissue, reducing the injection frequency of the collagen filler, and effectively reducing the use cost of such preparations. The collagen filler prepared according to the method of the present invention may have a multi-level pore size, such as a multi-level pore size of two or more combinations of a larger pore size and a smaller pore size in the range of 50 μm to 500 μm, for example, a multi-level pore size of two or more combinations of a smaller pore size of 50 μm to 120 μm and a larger pore size of 120 μm to 400 μm. The invented collagen filler with multi-level pore size also exhibits excellent mechanical performance, which is manifested as a higher dynamic viscosity. This may be due to the fact that the pores are connected by cross-linked collagen mesh fibers, so that it still maintains a high viscosity under the action of shear force, which greatly reduces the risk of displacement of the product after implantation into the tissue, and is more suitable for filling and repairing moderate to severe gravity wrinkles. In terms of biological performance, in addition to ensuring sterility and endotoxin inspection, its cytotoxicity test results show that the collagen filler of the present invention has a cell growth rate of at least 110% to 120%, indicating that the filler has good biocompatibility, further confirming the biosafety of the collagen filler of the present invention.

[0246] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A collagen filler, wherein the average pore size D of the collagen filler is 50 The collagen filler is prepared by the following preparation method, which comprises the following steps: (1) providing collagen and dissolving the collagen, wherein the concentration of the dissolved collagen solution is 0.5-15 mg / mL, and optionally filtering and sterilizing, wherein the processing temperature is 0° C. to 25° C.; (2) adding a buffer solution, adjusting the pH to 6-8, and stirring to form a collagen suspension; (3) adding microspheres and stirring until uniform, wherein the average particle size of the microspheres is 50 μm to 500 μm, and the stacking volume of the microspheres is 0.1% to 10% relative to the total volume of the collagen suspension; (4) adding a cross-linking agent, adjusting the pH to 8.0 to 12.0, adjusting the temperature to 20-40° C., and carrying out a cross-linking reaction under constant temperature conditions for a reaction time of 6 h to 8 days, wherein: The cross-linking agent is any one or more of epoxide cross-linking agents, and the concentration of the cross-linking agent is 0.005%-3.0%; (5) sieving the suspension while stirring, and adjusting the sieve mesh size to be smaller than the diameter of the microspheres to remove the microspheres in the suspension; (6) Optionally neutralize, purify and homogenize. 2 . The collagen filler according to claim 1 , wherein the porosity of the collagen filler is 80%-100%.

3. The collagen filler according to claim 1 or 2, wherein the degree of cross-linking of the collagen filler is 10% to 70%.

4. The collagen filler according to claim 1 or 2, wherein the degradation loss rate of the collagen filler is less than 40%.

5. The collagen filler according to claim 1 or 2, wherein the collagen filler has a dynamic viscosity of 90,000 to 300,000 mPa.s at a shear rate of 2 Hz and a temperature of 25±1°C.

6. The collagen filler according to claim 1 or 2, wherein the melting point of the collagen filler is 55°C to 85°C.

7. The collagen filler according to claim 1 or 2, wherein the collagen filler comprises a combination of different pore sizes, a combination of one or more pore sizes of 50 μm to 120 μm and one or more pore sizes of 120 μm to 500 μm.

8. The collagen filler according to claim 1 or 2, wherein the collagen filler has an average pore size D 50 The nanostructured carbon fiber has a thickness of 50 μm to 500 μm, a porosity of 80% to 100%, a cross-linking degree of 10% to 70%, and an in vitro enzymatic degradation loss rate of less than 40%.

9. The collagen filler according to claim 1, wherein the average pore size D of the collagen filler is 50 80μm to 400μm.

10. The collagen filler according to claim 1, wherein the average pore size D of the collagen filler is 50 90μm to 300μm.

11. The collagen filler according to claim 1, wherein the average pore size D of the collagen filler is 50 100μm to 250μm.

12. The collagen filler according to claim 1, wherein the average pore size D of the collagen filler is 50 120μm to 200μm.

13. The collagen filler according to claim 2, wherein the porosity of the collagen filler is 85%-100%.

14. The collagen filler according to claim 2, wherein the porosity of the collagen filler is 90%-100%.

15. The collagen filler according to claim 3, wherein the cross-linking degree of the collagen filler is 12% to 65%.

16. The collagen filler according to claim 3, wherein the cross-linking degree of the collagen filler is 15% to 60%.

17. The collagen filler according to claim 3, wherein the cross-linking degree of the collagen filler is 18% to 55%.

18. The collagen filler according to claim 3, wherein the cross-linking degree of the collagen filler is 20% to 50%.

19. The collagen filler according to claim 4, wherein the degradation loss rate of the collagen filler is less than 35%.

20. The collagen filler according to claim 4, wherein the degradation loss rate of the collagen filler is less than 30%.

21. The collagen filler according to claim 4, wherein the degradation loss rate of the collagen filler is less than 25%.

22. The collagen filler according to claim 4, wherein the degradation loss rate of the collagen filler is less than 20%.

23. The collagen filler according to claim 5, wherein the collagen filler has a dynamic viscosity of 95000 mPa.s to 280000 mPa.s at a shear rate of 2 Hz and a temperature of 25±1°C.

24. The collagen filler according to claim 5, wherein the collagen filler has a dynamic viscosity of 98000 mPa.s to 270000 mPa.s at a shear rate of 2 Hz and a temperature of 25±1°C.

25. The collagen filler according to claim 5, wherein the collagen filler has a dynamic viscosity of 100,000 to 260,000 mPa.s at a shear rate of 2 Hz and a temperature of 25±1°C.

26. The collagen filler according to claim 5, wherein the collagen filler has a dynamic viscosity of 120,000 to 250,000 mPa.s at a shear rate of 2 Hz and a temperature of 25±1°C.

27. The collagen filler according to claim 6, wherein the melting point of the collagen filler is 58°C to 80°C.

28. The collagen filler according to claim 6, wherein the melting point of the collagen filler is 60°C to 78°C.

29. The collagen filler according to claim 6, wherein the melting point of the collagen filler is 62°C to 75°C.

30. The collagen filler according to claim 6, wherein the melting point of the collagen filler is greater than 65°C.

31. The collagen filler according to claim 6, wherein the melting point of the collagen filler is lower than 73°C.

32. The collagen filler according to claim 7, wherein the collagen filler comprises a combination of different pore sizes, a combination of one or more pore sizes of 50 μm to 100 μm and one or more pore sizes of 120 μm to 450 μm.

33. The collagen filler according to claim 7, wherein the collagen filler comprises a combination of different pore sizes, a combination of one or more pore sizes of 50 μm to 90 μm and one or more pore sizes of 130 μm to 420 μm.

34. The collagen filler according to claim 7, wherein the collagen filler comprises a combination of different pore sizes, a combination of one or more pore sizes of 50 μm to 80 μm and one or more pore sizes of 140 μm to 400 μm.

35. A method for preparing a collagen filler according to any one of the preceding claims, comprising the following steps: (1) providing collagen and dissolving the collagen, wherein the concentration of the dissolved collagen solution is 0.5-15 mg / mL, and optionally filtering and sterilizing, wherein the processing temperature is 0° C. to 25° C.; (2) adding a buffer solution, adjusting the pH to 6-8, stirring, and forming a collagen suspension, wherein the volume ratio of the collagen solution to the buffer solution is 20:1 to 5:1; (3) adding microspheres and stirring until uniform, wherein the average particle size of the microspheres is 50 μm to 500 μm, and the stacking volume of the microspheres is 0.1% to 10% relative to the total volume of the collagen suspension; (4) adding a cross-linking agent, adjusting the pH to 8.0 to 12.0, adjusting the temperature to 20-40° C., and carrying out a cross-linking reaction under constant temperature conditions for a reaction time of 6 h to 8 days, wherein: The cross-linking agent is any one or more of epoxide cross-linking agents, and the concentration of the cross-linking agent is 0.005%-3.0%; (5) sieving the suspension while stirring, and adjusting the sieve mesh size to be smaller than the diameter of the microspheres to remove the microspheres in the suspension; (6) Optionally neutralize, purify and homogenize.

36. The method according to claim 35, wherein in step (1), collagen is dissolved in a 0.001-0.1 mol / L acid solution.

37. The method according to claim 35, wherein in step (1), the dissolving of collagen is carried out under stirring.

38. The method according to claim 36, wherein in step (1), the dissolving of collagen is carried out under stirring.

39. The method according to claim 35 or 36, wherein in step (1), the treatment temperature is 1°C to 20°C.

40. The method according to claim 35 or 36, wherein in step (2), the buffer solution is selected from a phosphate buffer solution.

41. The method according to claim 35 or 36, wherein in step (2), the concentration of the buffer solution is 0.05-0.5 mol / L.

42. The method according to claim 35 or 36, wherein in step (2), the volume ratio of the collagen solution to the buffer solution is 15:1 to 6:

1.

43. The method according to claim 35 or 36, wherein in step (2), the pH is adjusted to 6 to 8.

44. The method according to claim 35 or 36, wherein in step (2), the treatment temperature is 20°C to 37°C.

45. The method according to claim 35 or 36, wherein steps (3) to (5) are repeated multiple times, wherein the average particle size of the microspheres is different.

46. ​​The method according to claim 35 or 36, wherein the microspheres are made of an inert biomedical material.

47. The method according to claim 35 or 36, wherein the average particle size of the microspheres is 80 μm to 400 μm.

48. A method according to claim 35 or 36, wherein: The bulk volume of the microspheres was 0.2% to 8% relative to the total volume of the collagen suspension.

49. The method according to claim 35 or 36, wherein in step (3), the treatment temperature is 20°C to 37°C.

50. The method according to claim 35 or 36, wherein steps (3) to (5) are repeated 2-5 times, wherein the particle size of the microspheres used in each step (3) to (5) is different.

51. The method according to claim 37, wherein steps (3) to (5) are repeated 2-5 times, wherein the particle size of the microspheres used in each step (3) to (5) is different.

52. The method according to claim 38, wherein steps (3) to (5) are repeated 2-5 times, wherein the particle size of the microspheres used in each step (3) to (5) is different.

53. The method according to claim 39, wherein steps (3) to (5) are repeated 2-5 times, wherein the particle size of the microspheres used in each step (3) to (5) is different.

54. The method according to claim 40, wherein steps (3) to (5) are repeated 2-5 times, wherein the particle size of the microspheres used in each step (3) to (5) is different.

55. The method according to claim 41, wherein steps (3) to (5) are repeated 2-5 times, wherein the particle size of the microspheres used in each step (3) to (5) is different.

56. The method according to claim 42, wherein steps (3) to (5) are repeated 2-5 times, wherein the particle size of the microspheres used in each step (3) to (5) is different.

57. The method according to claim 35 or 36, wherein in the purification step, the product is collected by centrifugation at a speed of >5000 rpm.

58. A method according to claim 35 or 36, wherein: During the purification step, the concentration of phosphate buffer was 0.05-0.30 mol / L.

59. The method according to claim 35 or 36, wherein in the purification step, the amount of phosphate buffer added each time is 6-10 times of the centrifugal precipitate, and the precipitate is washed more than or equal to 5 times to remove the cross-linking agent in the cross-linked collagen suspension.

60. The method according to claim 35 or 36, further comprising a homogenization step, wherein the product is poured into a homogenizer and homogenized until uniform.

61. The method according to claim 35 or 36, further comprising a filling step, wherein the homogenized sample is filled into a syringe, and after inner and outer packaging, a collagen filler is obtained.

62. The method according to claim 35 or 36, wherein the following steps are performed in sequence: (1) dissolving collagen extracted from tissue in an acid solution of 0.001 mol / L to 0.1 mol / L; (2) adding a phosphate buffer solution, adjusting the pH to 6-8, and stirring at 20-37° C. until the collagen solution precipitates to form a suspension; (3) Add microspheres and continue stirring at 20-37°C until uniform; (4) adding a cross-linking agent, adjusting the temperature to 20-40° C., and reacting under constant temperature conditions for 6 h to 8 days; (5) sieving the suspension while stirring, and adjusting the sieve mesh size to be smaller than the diameter of the microspheres to remove the microspheres in the suspension; (6) collecting the product by centrifugation and washing it with phosphate buffer to remove the cross-linking agent; (7) Homogenization: Pour the product into a homogenizer and homogenize until uniform; (8) Optionally, the homogenized sample is filled into a syringe to obtain a collagen filler.

63. A method according to claim 62, wherein steps (3) to (5) are repeated 2-5 times, wherein the particle size of the microspheres used in each implementation of steps (3) to (5) is different, selected from a combination of one or more particle sizes of 50 μm to 120 μm and one or more particle sizes of 120 μm to 500 μm.

64. The method according to claim 62, wherein in step (1), the concentration of the dissolved collagen solution is 0.8-12 mg / mL.

65. The method according to claim 62, wherein in step (1), the concentration of the dissolved collagen solution is 1.0 to 10 mg / mL.

66. The method according to claim 62, wherein in step (1), the concentration of the dissolved collagen solution is 1.5-8 mg / mL.

67. The method according to claim 62, wherein in step (1), the concentration of the dissolved collagen solution is 2.0-6 mg / mL.

68. The method according to claim 62, wherein in step (1), the collagen is dissolved in a 0.001-0.1 mol / L acid solution selected from hydrochloric acid, phosphoric acid, acetic acid, citric acid, or a mixture thereof.

69. The method according to claim 62, wherein in step (1), the collagen is dissolved under stirring for 1 hour to 5 days.

70. The method according to claim 62, wherein in step (1), the collagen is dissolved under stirring for 6 hours to 4 days.

71. The method according to claim 62, wherein in step (1), the dissolution of collagen is carried out under stirring for 12 hours to 3 days.

72. The method according to claim 62, wherein in step (1), the dissolution of collagen is carried out under stirring for 24 hours to 2 days.

73. The method according to claim 62, wherein in step (1), the treatment temperature is 2°C to 10°C.

74. The method according to claim 62, wherein in step (1), the treatment temperature is 4°C to 8°C.

75. The method according to claim 62, wherein in step (2), the buffer solution is selected from phosphate / hydrogen phosphate buffer solution, citrate buffer solution, Tris buffer, potassium dihydrogen phosphate-sodium hydroxide buffer, and disodium hydrogen phosphate-citric acid buffer.

76. The method according to claim 62, wherein in step (2), the concentration of the buffer solution is 0.06-0.3 mol / L.

77. The method according to claim 62, wherein in step (2), the concentration of the buffer solution is 0.08-0.25 mol / L.

78. The method according to claim 62, wherein in step (2), the concentration of the buffer solution is 0.09-0.2 mol / L.

79. The method according to claim 62, wherein in step (2), the volume ratio of the collagen solution to the buffer solution is 12:1 to 7:

1.

80. The method according to claim 62, wherein in step (2), the volume ratio of the collagen solution to the buffer solution is 10:1 to 8:

1.

81. The method according to claim 62, wherein in step (2), the pH is adjusted to 6.5 to 7.

5.

82. The method according to claim 62, wherein in step (2), the pH is adjusted to 6.8 to 7.

3.

83. The method according to claim 62, wherein in step (2), the pH is adjusted to 6.9 to 7.

2.

84. The method according to claim 62, wherein in step (2), the treatment temperature is 25°C to 35°C.

85. The method according to claim 62, wherein in step (2), the treatment temperature is 27°C to 34°C.

86. The method according to claim 62, wherein in step (2), the treatment temperature is 30°C to 33°C.

87. The method according to claim 62, wherein steps (3) to (5) are repeated 2-5 times, wherein the average particle size of the microspheres is different.

88. The method according to claim 62, wherein steps (3) to (5) are repeated 2 or 3 times, wherein the average particle size of the microspheres is different.

89. The method according to claim 62, wherein the microspheres are selected from inert bioceramic microspheres, medical metal microspheres, and inert polymer material microspheres.

90. The method according to claim 62, wherein the microspheres are selected from alumina ceramic microspheres, titanium alloy microspheres, polytetrafluoroethylene microspheres, titanium silicon microspheres, polymethyl methacrylate microspheres, hydroxyapatite microspheres, poly-L-lactic acid microspheres, and polycaprolactone microspheres.

91. The method according to claim 62, wherein the average particle size of the microspheres is 90 μm to 300 μm.

92. The method according to claim 62, wherein the average particle size of the microspheres is 100 μm to 250 μm.

93. The method according to claim 62, wherein the average particle size of the microspheres is 120 μm to 200 μm.

94. The method according to claim 62, wherein: The bulk volume of the microspheres was 0.3% to 6% relative to the total volume of the collagen suspension.

95. The method according to claim 62, wherein: The bulk volume of the microspheres was 0.4% to 5% relative to the total volume of the collagen suspension.

96. The method according to claim 62, wherein: The bulk volume of the microspheres was 0.5% to 4% relative to the total volume of the collagen suspension.

97. The method according to claim 62, wherein: The bulk volume of the microspheres was 1-3% relative to the total volume of the collagen suspension.

98. The method according to claim 62, wherein in step (3), the treatment temperature is 25°C to 35°C.

99. The method according to claim 62, wherein in step (3), the treatment temperature is 27°C to 34°C.

100. The method according to claim 62, wherein in step (3), the treatment temperature is 30°C to 33°C.

101. The method according to claim 62, wherein in step (4), the cross-linking agent is selected from sorbitol, glycerol, and 1,4-butanediol diglycidyl ether.

102. The method according to claim 62, wherein in step (4), the concentration of the cross-linking agent is 0.010%-2.0%.

103. The method according to claim 62, wherein in step (4), the concentration of the cross-linking agent is 0.015%-1.5%.

104. The method according to claim 62, wherein in step (4), the concentration of the cross-linking agent is 0.02%-1.0%.

105. The method according to claim 62, wherein in step (4), the concentration of the cross-linking agent is 0.025%-0.5%.

106. The method according to claim 62, wherein in step (4), the pH is adjusted to 8.5 to 11.

5.

107. The method according to claim 62, wherein in step (4), the pH is adjusted to 9.0 to 11.

0.

108. The method according to claim 62, wherein in step (4), the pH is adjusted to 9.5 to 10.

5.

109. The method according to claim 62, wherein in step (4), the reaction temperature is 25°C to 37°C.

110. The method according to claim 62, wherein in step (4), the reaction temperature is 28°C to 36°C.

111. The method according to claim 62, wherein in step (4), the reaction temperature is 30°C to 35°C.

112. The method according to claim 62, wherein in step (4), the reaction time is from 12 h to 6 days.

113. The method according to claim 62, wherein in step (4), the reaction time is 36 h to 5 days.

114. The method according to claim 62, wherein in step (4), the reaction time is 2 to 4 days.

115. A method according to claim 62, wherein steps (3) to (5) are repeated 2-5 times, wherein the particle size of the microspheres used in each implementation of steps (3) to (5) is different, selected from a combination of one or more particle sizes of 50 μm to 120 μm and one or more particle sizes of 120 μm to 500 μm.

116. A method according to claim 62, wherein steps (3) to (5) are repeated 2-5 times, wherein the particle size of the microspheres used in each implementation of steps (3) to (5) is different, selected from a combination of one or more particle sizes of 50 μm to 100 μm and one or more particle sizes of 120 μm to 450 μm.

117. A method according to claim 62, wherein steps (3) to (5) are repeated 2-5 times, wherein the particle size of the microspheres used in each implementation of steps (3) to (5) is different, selected from a combination of one or more particle sizes of 50 μm to 90 μm and one or more particle sizes of 130 μm to 420 μm.

118. A method according to claim 62, wherein steps (3) to (5) are repeated 2-5 times, wherein the particle size of the microspheres used in each implementation of steps (3) to (5) is different, selected from a combination of one or more particle sizes of 50 μm to 80 μm and one or more particle sizes of 140 μm to 400 μm.

119. The method according to claim 62, wherein in the purification step, the product is collected by centrifugation at a speed of >5000 rpm and repeatedly washed more than 5 times with 5-50 volumes of phosphate buffer to remove the cross-linking agent.

120. The method according to claim 62, wherein: In the purification step, the concentration of phosphate buffer is 0.08-0.20 mol / L.

121. The method according to claim 62, wherein: During the purification step, the concentration of phosphate buffer was 0.09-0.15 mol / L.

122. The method according to claim 62, wherein: During the purification step, the concentration of phosphate buffer was 0.10-0.12 mol / L.

123. The method according to claim 62, further comprising a homogenization step, wherein the product is poured into a homogenizer and homogenized until uniform, and the homogenization is cyclically repeated for more than or equal to 2 times.

124. The method according to claim 62, further comprising a homogenization step, wherein the product is poured into a homogenizer and homogenized until uniform, and the homogenization is cyclically performed for more than or equal to 3 times.

125. The method according to claim 62, wherein the microspheres are selected from alloy-based microspheres.

126. Use of the collagen filler according to any one of the preceding claims 1 to 34 and in products according to pre-plastic surgery, surgery or surgical treatment fillers.

127. Use according to claim 126, wherein: The medical plastic surgery is selected from the treatment of fine lines, facial sculpting and correction.

Citation Information

Patent Citations

  • Triple cross-linking collagen, preparation method and uses thereof

    CN102924731B

  • Composition, preparation method and application of dual-crosslinking collagen filler

    CN114288469A

  • Preparation method of collagen sponge with pore size self-adaptive adjusting capability and collagen sponge

    CN107349456A

  • Differentially biodegradable biomedical implants

    WO1996010374A1

Cited By

  • Preparation method and application of recombinant I-type human collagen filler

    CN120733120A

  • A preparation method and application of a recombinant type I human collagen filler

    CN120733120B